(3eLdI JHjGf ddOQGSGJ GdbQBfjI (B/s (3eLdI YdejI OhQjI eMceI (B.s - (3GdLeYjI GdYdejI GdSYhOjI ddbQBf GdcQje hYdheg (B.s; (3GdTGjY, eMeO Hf YHO GdQMefs; (3GdLeYjI GdYdejI GdSYhOjI ddbQBf GdcQje hYdheg (B((3GdQjGV(B)s ((3GdeedcI GdYQHjI GdSYhOjI (B:s (3GdLeYjI GdYdejI GdSYhOjI ddbQBf GdcQje hYdheg(B.s, 2007)
(3aj GdOQGSGJ GdbQBfjI(B.s
(3eSJeQg GdUOQhs
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
Keywords: (3GdbQBfs -- (3Ydhes -- (3OhQjGJs; (3GdbQBfs -- (3HMhKs -- (3OhQjGJs